Delivery of a Schistosomus reflexus monster through caesarean section in a Murrah buffalo - Dutt, Ravi; Singh, Gyan; -, Jasmer; Chandolia, R. K. (Buffalo Bulletin, 2019)
A case of dystocia in a Murrah buffalo due to Schistosomus reflexus monster is reported and discussed here.